Analysis Of The Application Of Pancasila Student Profile In The Character Forming to Students In Elementary School - Maria Margareta Sartika,; Wilasih,; Tjio Dedy, (International Conference on Elementary Education, 2023)
This study aims to determine the strategies used by the teacher in implementing the Pancasila student profile to shape the character of students. This research was conducted at SD Santa Ursula Bandung. The type of research used is descriptive qualitative, which describes the implementation of the Pancasila student profile and the strategies used by the teacher in making it happen. The subjects studied were first-grade students consisting of 26 students. Data collection techniques used are Observation, Interview and Documentation. From the observations, the researchers found the strategies used by teachers in implementing the Pancasila Student Profile, including; differentiation learning, learning by project and habituation. From the results of research conducted by researchers, the teacher has implemented the strategy well. This is evidenced by the existence of data on the value of lessons and documentation of student activities. In the successful application of this strategy, the teacher must be creative in designing learning. In addition to the role of the teacher, the family and social environment also play a role in shaping the character of students.